Teori Perkembangan Sosial Emosi Erikson dan Tahap Perkembangan Moral Kohlberg: Penerapan di Sekolah - Habsy, Bakhrudin All; Armania, Selomita Dianing; Maharani, Alifia Putri; Fatimah, Siti (TSAQOFAH, 2024)
Erikson's theory of social emotional development and Kohlberg's moral development can be applied in school life to determine the development of students' moral reasoning and also determine students' social interaction relationships. With Erikson's theory of social development, we can understand the stages of human development starting from our sensitivity and ability to adapt to the surrounding environment. The purpose of this article is to determine the implementation of Guidance Counseling on improving children's morals at school and to determine whether or not there is an influence of Guidance Counseling on improving children's morals. The aim of this research is also to provide a way for adolescents to find their identity and synthesize the stages of adolescent psychosocial development.